Identifying the barriers faced by medical students using virtual reality simulation - James Lloyd; Sohail Akhtar; Packianathaswamy Balaji (Discover Education, 2023)
Abstract Background Virtual reality technology is increasingly used in medical education to facilitate immersive experiences allowing users to interact with a simulated environment to foster learning. However, the potential barriers to this experience from a user perspective have not been fully explored. Methods Twenty final-year medical students participated in answering a pre- and post-simulation questionnaire as part of a facilitated virtual reality simulation session. The questionnaire explored participants’ expectations and experiences of virtual reality, in relation to adverse effects, interest and usefulness through 0–10 rating scales. Free-text questioning was used for further discussion. Results Ratings of all assessed adverse symptoms experienced by students were significantly lower than their expected ratings (p < 0.01), and ratings of reported usefulness and interest in virtual reality significantly increased post-simulation (p < 0.01). The median ratings given for all symptoms experienced by students were either 0 or 1/10 (none/minimal). Free-text comments raised problems of visual focussing in those who wear glasses. Discussion Our results suggest that virtual reality is an appropriate simulation modality which is acceptable to students. Potential barriers such as cybersickness and discomfort were minimally experienced and did not impact reported usefulness. We promote the generalisability of these findings by demonstrating them on commonly used consumer equipment and a common use case.